Gestão democrática, educação e cidadania: um olhar crítico a partir de fontes bibliográficas - Dias, Adriana Marques Guimarães [UNESP] (2015)
The democratic management of education in Brazil emerged from social movements of teachers who demanded a public school education, universal, secular and free in the 1980s that sense, democratic management countered to the school administration, which gradually ceased to be part of educational literature on the subject, as well as education laws (SILVA JUNIOR, 2002). So, in the face of social pressures, democratic management has become a legal principle in the Federal Constitution of 1988, which was then reflected in the Ten Year Plan for Education (1993), in LDBEN 9394/96, the National Education Plan - 2001-201, unfolding in the Education Development Plan - PDE (Adrião & Camargo, 2007; Saviani, 2006, 2008). Therefore, we sought to understand what ideological implications underlay the amendment. Therefore, we have adopted procedures of literature (GIL (2002)), using Brazilian authors of literary texts on business administration (TAYLOR (1856-1915), Fayol (1841-1925), CHIAVENATO (1983), Motta (1991), TRAGTEMBERG (1974), school administration (FELIX (1989), LION ARIES (1887-1966), SON LORENZO (1897-1970), QUERINO RIBEIRO (1907-1990), Teixeira (1900-1971), Myrtes Alonso (1976), BRUNO (1997)), school management (SANDER, (2005), PARO (2010)) and democratic management (ARROYO (2008), PARO (2003, 2008), VEIGA (1995), LUCK (2000 ), SILVA JUNIOR (2002)) and the above laws and guidelines of multilateral organizations such as the Economic Commission for Latin America and the Caribbean (ECLAC), the International Monetary Fund (IMF) and the World Bank (WB), that produced documents as the Priorities and Strategies for Education: sectoral World Bank study, and the United Nations Educational, Science and Culture (UNESCO), responsible for organizing the World Conference on Education for All and the document World Declaration on Education for All - Meeting the Basic Learning Needs, in 1993. In addition, we rely on academic research on the ...